2009
DOI: 10.1074/jbc.m109.014860
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Liver X Receptor Stimulates Trans-intestinal Excretion of Plasma Cholesterol

Abstract: Recent studies have indicated that direct intestinal secretion of plasma cholesterol significantly contributes to fecal neutral sterol loss in mice. The physiological relevance of this novel route, which represents a part of the reverse cholesterol transport pathway, has not been directly established in vivo as yet. We have developed a method to quantify the fractional and absolute contributions of several cholesterol fluxes to total fecal neutral sterol loss in vivo in mice, by assessing the kinetics of orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
217
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(231 citation statements)
references
References 45 publications
9
217
1
4
Order By: Relevance
“…Preliminary data suggest that fecal cholesterol contents of Vil-Insig ؊ mice seem to be slightly higher than that of control mice under chow-fed conditions. Future quantitative whole-body cholesterol balance studies, such as the method developed by van der Vee et al (39), will be necessary to elucidate the potential alterations of TICE in VilInsig ؊ mice. The effect of increasing intestinal cholesterol synthesis on the liver is reminiscent of the effect of feeding cholesterol-rich diets.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data suggest that fecal cholesterol contents of Vil-Insig ؊ mice seem to be slightly higher than that of control mice under chow-fed conditions. Future quantitative whole-body cholesterol balance studies, such as the method developed by van der Vee et al (39), will be necessary to elucidate the potential alterations of TICE in VilInsig ؊ mice. The effect of increasing intestinal cholesterol synthesis on the liver is reminiscent of the effect of feeding cholesterol-rich diets.…”
Section: Discussionmentioning
confidence: 99%
“…Enfin, ce même groupe a démontré que le TICE est principalement actif dans la partie proximale de l'intestin ; les auteurs ont estimé que, chez des souris C57BL6, 33 % du cholestérol fécal proviendraient du TICE, alors que 17 % proviendraient de la voie biliaire. Ces résultats font du TICE une voie majeure d'épuration du cholestérol de l'organisme [9]. Cependant, la contribution relative cette voie à l'excrétion fécale de cholestérol est probablement dépendante du fonds génétique de la souris étudiée ; chez les souris FVB (Friend virus B-type), la contribution du TICE serait de 20 % [6].…”
Section: Identification Des Transporteurs De Cholestérol Impliqués Daunclassified
“…Plösch et al ont montré que l'activation des récepteurs nucléaires LXR (liver X receptor) augmente l'excrétion fécale de cholestérol de façon similaire chez les souris sauvages et les souris invalidées pour le transporteur ABCA1, chez lesquelles on observe une quasi absence de HDL circulants [12]. De même, les agonistes LXR, des stimulateurs reconnus du TICE (voir plus loin [6,9]), réduisent dans les mêmes conditions expérimentales l'accumulation intestinale d'éther de cholestérol (cholestérol non métabolisable) provenant d'HDL, faisant douter de l'importance fonctionnelle des HDL dans le TICE [13]. Deux études récentes ont mesuré de façon directe le TICE après une injection intraveineuse d'HDL marqués au cholestérol radioactif.…”
unclassified
“…Around 20% -33% of basal fecal sterol loss has been estimated due to TICE in both human [56] and mice [57]. It has been shown that the non-biliary TICE pathway can be stimulated by activation of LXR [57] and PPARδ [58], ezetimibe administration [59], and fasting [60]. However, the precise underlying mechanisms and pathways for the induction of TICE are still unknown.…”
Section: Intestinal Cholesterol Absorptionmentioning
confidence: 99%
“…Although TICE can occur throughout the small intestine, but most of the TICE happens in the proximal intestine [55]. Around 20% -33% of basal fecal sterol loss has been estimated due to TICE in both human [56] and mice [57]. It has been shown that the non-biliary TICE pathway can be stimulated by activation of LXR [57] and PPARδ [58], ezetimibe administration [59], and fasting [60].…”
Section: Intestinal Cholesterol Absorptionmentioning
confidence: 99%